1700MPa-grade hot-formed steel with high cold bending performance as well as preparation method and application of 1700MPa-grade hot-formed steel

By introducing mixed structures of ferrite and martensite to the surface of the thermoformed steel and adjusting the preparation conditions, the contradiction between strength and toughness of the thermoformed steel is solved, and a 1700MPa-grade high cold bending performance is achieved, which meets the lightweight requirements and improves the competitiveness of the product.

CN119530651AActive Publication Date: 2025-02-28BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD

Patent Information

Application Number
CN202411708859.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

Existing thermoformed steels are difficult to balance between strength and toughness, and are difficult to meet the lightweight requirements, resulting in the risk of premature material failure in applications in energy-absorbing areas.

Method used

By introducing 5-40 μm of ferrite and mixed structure of ferrite and martensite into the surface layer of the thermoformed steel, and the key preparation conditions are reasonably adjusted. For example, the coiling temperature after hot rolling is 650-700℃, the pickling speed is ≤150m/min, the continuous annealing temperature is 780-830℃, the atmosphere in the furnace is a mixture of nitrogen and hydrogen, and the dew point temperature is -35℃ to -17℃.

Benefits of technology

Thermoformed steel with high cold bending performance achieved 1700MPa grade has a strength of 200MPa higher than that of commercial 1500MPa grade thermoformed steel, and its bending toughness is comparable, which solves the contradiction between material strength and toughness, meets the requirements of lightweighting, and improves the competitiveness of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530651A_ABST
    Figure CN119530651A_ABST
Patent Text Reader

Abstract

The invention provides 1700MPa-grade hot-formed steel with high cold bending performance and a preparation method and application thereof. The surface layer of the hot-formed steel has a soft-phase ferrite structure, the secondary surface layer of the hot-formed steel has a mixed structure of soft-phase ferrite and martensite, and the core layer of the hot-formed steel has a carbon-poor martensite structure. The preparation method comprises any one or a combination of at least two of the following conditions: (A) the coiling temperature after hot rolling is 650-700 DEG C; (B) the pickling speed is less than or equal to 150m / min; (C) the continuous annealing temperature is 780-830 DEG C; (D) the atmosphere in the furnace is mixed gas of nitrogen and hydrogen; and (E) the dew point temperature is-35 DEG C to-17 DEG C. Through fine component design and process integration, the contradiction between the strength and the toughness of the material is successfully solved, double guarantee of high strength and high toughness is achieved, meanwhile, the requirement for light weight is met, and the competitiveness of an existing product is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of alloy materials and relates to a hot-formed steel, in particular to a 1700MPa-grade hot-formed steel with high cold bending performance and a preparation method and application thereof. Background Art

[0002] Hot stamping technology is a highly promising process for producing high-strength steel parts. It not only significantly improves the strength of the material through martensitic phase transformation, but also more effectively reduces the springback of parts compared to cold stamping. At present, the strength of hot-formed steel is mainly concentrated in the range of 500-2000MPa, and the principle of material selection follows "using the right material in the right place". For example, the upper part of the B-pillar usually requires high strength to provide sufficient resistance to intrusion, while the lower part requires high toughness to absorb the impact energy generated during the collision. However, in recent years, with the gradual advancement of lightweight requirements, manufacturers have proposed the concept of using ultra-high-strength steel in energy-absorbing areas to achieve weight reduction effects. It is worth noting that the material in the energy-absorbing area must have sufficiently high bending toughness to avoid premature failure during use. To this end, researchers in the industry have conducted in-depth exploration and research on this issue from aspects such as component design and process improvement.

[0003] In terms of composition design, the toughness of hot-formed steel is improved by adding microalloying elements or composite additions. For example, CN106399837A refines the grains by adding vanadium (V) microalloys, and uses precipitated particles to consume carbon (C) to reduce the proportion of brittle twin martensite, thereby improving its toughness; CN106947919A ensures the presence of a small amount of residual austenite in the final structure by adding manganese (Mn), and uses niobium (Nb) and titanium (Ti) composite additions to refine the grains to improve toughness. Although the above strategies have played a certain role in improving toughness, the effect is limited and still does not fully meet the technical requirements.

[0004] In terms of process optimization, CN115058650A adopts a rapid heating method to obtain a martensitic matrix-submicron residual austenite-nanocarbide complex structure by regulating the cementite in the steel, so that the hot-formed steel has both high strength and high toughness; CN116174558A adopts a two-step heating method to significantly improve the bending toughness. First, the material is heated to 950-1100°C to form a 5-100μm ferrite diffusion layer, and then to prevent the austenite grain size from growing during the high-temperature heating process, a secondary low-temperature heating (800-870°C) is performed to refine the original austenite grain size, thereby achieving an improvement in bending toughness. Although both of the above methods can significantly improve bending toughness, they are difficult to promote and apply on a large scale due to the complex process and the volatility of material properties.

[0005] It can be seen that how to provide a hot-formed steel with high cold bending performance and a preparation method thereof, which has both high strength and high toughness while meeting lightweight requirements, has become an urgent problem that technical personnel in this field need to solve. Summary of the invention

[0006] The purpose of the present invention is to provide a 1700MPa grade hot-formed steel with high cold bending performance and a preparation method and application thereof. Through fine component design and process integration, the contradiction between material strength and toughness is successfully resolved, and the dual guarantee of high strength and high toughness is achieved. At the same time, lightweight requirements are met, and the competitiveness of existing products is improved.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a 1700MPa grade hot-formed steel with high cold bending performance, wherein the hot-formed steel has a soft-phase ferrite structure on the surface, a mixed structure of soft-phase ferrite and martensite on the sub-surface, and a carbon-poor martensite structure in the core layer.

[0009] Wherein, the thickness of the surface layer is 0-20 μm, and the thickness of the sub-surface layer is 5-20 μm.

[0010] The tensile strength of the hot-formed steel is 1650-1750 MPa.

[0011] The present invention changes the distribution characteristics of the traditional full martensitic structure, introduces 5-40μm ferrite and a mixed structure of ferrite and martensite into the surface layer of the hot-formed steel, and uses the synergistic effect between the ferrite structure and the martensite structure. At the same time, the thickness range of each layer is limited to obtain a hot-formed steel with high cold bending performance of 1700MPa. While ensuring that the strength is 200MPa higher than that of commercial 1500MPa hot-formed steel, the bending toughness is equivalent, which successfully solves the contradiction between material strength and toughness, achieves the dual guarantee of high strength and high toughness, meets the lightweight requirements, and improves the competitiveness of existing products.

[0012] Preferably, the carbon content of the carbon-poor martensite structure is 50%-90% of the target carbon content in the hot forming steel.

[0013] Preferably, the core layer also contains ferrite structure, and the proportion of the ferrite structure in the core layer is ≤5wt%.

[0014] Preferably, the chemical composition of the hot forming steel comprises, by mass percentage:

[0015]

[0016] The balance includes Fe and inevitable impurities.

[0017] Preferably, in terms of mass percentage, C+Al+Si≥1.0%, Cr+Mn≤3.0%, and (Cr+Mn) / (C+Al+Si)≤1.5%.

[0018] Preferably, in terms of mass percentage, Nb+V≤0.05%.

[0019] Preferably, in terms of mass percentage, the welding carbon equivalent CE=C+Mn / 6+(Cr+Mo+V) / 5+(Ni+Cu) / 15<0.5%.

[0020] Preferably, in terms of mass percentage, Si+Cr≤1.2%.

[0021] In a second aspect, the present invention provides a method for preparing the hot-formed steel as described in the first aspect, wherein the method satisfies any one or a combination of at least two of the following conditions:

[0022] (A) The coiling temperature after hot rolling is 650-700℃;

[0023] (B) Pickling speed ≤ 150m / min;

[0024] (C) The temperature of continuous annealing is 780-830°C;

[0025] (D) The atmosphere in the furnace is a mixture of nitrogen and hydrogen;

[0026] (E) The dew point temperature is -35°C to -17°C.

[0027] The present invention realizes sufficient decarburization and refines the grain structure by reasonably adjusting the key preparation conditions of hot-formed steel, further improves the toughness of the material, can replace safety parts with low strength and high toughness, achieves the purpose of weight reduction, and achieves a lightweight effect.

[0028] Preferably, the continuous annealing time is 8-12 minutes.

[0029] In a third aspect, the present invention provides an application of the hot-formed steel as described in the first aspect, wherein the hot-formed steel is used to manufacture body structural parts of an automobile, including seat cross beams, A-pillars, B-pillars, door anti-collision beams, front and rear bumpers, door sill beams or center channels.

[0030] The invention uses hot-formed steel to not only maintain or improve the safety and reliability of vehicle body components, but also significantly reduce vehicle weight, improve fuel efficiency, and thus reduce carbon emissions. This innovation will drive the automotive industry toward a more efficient and environmentally friendly direction, achieving a dual breakthrough in technology and materials.

[0031] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The present invention changes the distribution characteristics of the traditional full martensitic structure, introduces 5-40μm ferrite and a mixed structure of ferrite and martensite into the surface layer of the hot-formed steel, and rationally adjusts the key preparation conditions of the hot-formed steel, thereby achieving sufficient decarburization and refined grain structure. Finally, a 1700MPa-grade hot-formed steel with high cold bending performance is obtained. While ensuring that the strength is 200MPa higher than that of commercial 1500MPa-grade hot-formed steel, the bending toughness is comparable, which successfully solves the contradiction between material strength and toughness, achieves the dual guarantee of high strength and high toughness, meets the lightweight requirements, and improves the competitiveness of existing products. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is a micrograph of the decarburized layer of the hot-formed steel obtained in Example 1;

[0035] Figure 2 is a microstructure photograph of the hot-formed steel obtained in Example 1;

[0036] Figure 3 It is a comparison chart of the tensile and bending properties of the hot-formed steel obtained in Example 1 and the traditional 22MnB5 hot-formed steel. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0038] In order to have both high strength and high toughness while meeting the requirements of lightweight, the present invention provides a 1700MPa grade hot-formed steel with high cold bending performance, wherein the hot-formed steel has a soft phase ferrite structure on the surface, a mixed structure of soft phase ferrite and martensite on the sub-surface, and a carbon-poor martensite structure in the core layer.

[0039] Wherein, the thickness of the surface layer is 0-20μm, for example, it can be 0μm, 2μm, 4μm, 6μm, 8μm, 10μm, 12μm, 14μm, 16μm, 18μm or 20μm, and the thickness of the sub-surface layer is 5-20μm, for example, it can be 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] The tensile strength of the hot-formed steel is 1650-1750 MPa, for example, it can be 1650 MPa, 1660 MPa, 1670 MPa, 1680 MPa, 1690 MPa, 1700 MPa, 1710 MPa, 1720 MPa, 1730 MPa, 1740 MPa or 1750 MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] The present invention changes the distribution characteristics of the traditional full martensitic structure, introduces 5-40μm ferrite and a mixed structure of ferrite and martensite into the surface layer of the hot-formed steel, and uses the synergistic effect between the ferrite structure and the martensite structure. At the same time, the thickness range of each layer is limited to obtain a hot-formed steel with high cold bending performance of 1700MPa. While ensuring that the strength is 200MPa higher than that of commercial 1500MPa hot-formed steel, the bending toughness is equivalent, which successfully solves the contradiction between material strength and toughness, achieves the dual guarantee of high strength and high toughness, meets the lightweight requirements, and improves the competitiveness of existing products.

[0042] In some embodiments, the carbon content of the carbon-depleted martensite structure is 50%-90% of the target carbon content in the hot-formed steel, for example, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] In some embodiments, the core layer also has ferrite structure, and the proportion of the ferrite structure in the core layer is ≤5wt%, for example, it can be 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] In certain embodiments, the chemical composition of the hot forming steel includes, by weight percentage:

[0045]

[0046] The balance includes Fe and inevitable impurities.

[0047] Among them, the content of C is 0.20-0.30%, for example, it can be 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29% or 0.30%, the content of Si is 0.05-0.40%, for example, it can be 0.05%, 0.10%, 0.15%, 0.20%, 0.25%, 0.30%, 0.35% or 0.40%, and the content of Mn is 0.50-2.00%, for example, it can be 0.50%, 0.60%, 0.70%, 0.80%, 0.90%, 1.00%, 1.10%, 1.20%, 1.30%, 1.40%, 1.50%, The content of Cr is 0.20-1.00%, for example, 0.20%, 0.25%, 0.30%, 0.35%, 0.40%, 0.45%, 0.50%, 0.55%, 0.60%, 0.65%, 0.70%, 0.75%, 0.80%, 0.85%, 0.90%, 0.95% or 1.00%, the content of Al is 0.00-0.50%, for example, 0.00%, 0.05%, 0.10%, 0.15%, 0.20%, 0.25%, 0.30%, 0.35%, 0.40%, 0.45% or 0.50%, and the content of Nb is The content of B is 0.003-0.020%, for example, it can be 0.003%, 0.004%, 0.006%, 0.008%, 0.010%, 0.012%, 0.014%, 0.016%, 0.018% or 0.020%, the content of Ti is 0.01-0.05%, for example, it can be 0.01%, 0.02%, 0.03%, 0.04% or 0.05%, the content of Ni is 0.00-0.30%, for example, it can be 0.00%, 0.02%, 0.04%, 0.06%, 0.08%, 0.10% %, 0.12%, 0.14%, 0.16%, 0.18%, 0.20%, 0.22%, 0.24%, 0.26%, 0.28% or 0.30%, the content of Mo is 0.00-0.05%, for example, it can be 0.00%, 0.01%, 0.02%, 0.03%, 0.04% or 0.05%, the content of V is 0.00-0.05%, for example, it can be 0.00%, 0.01%, 0.02%, 0.03%, 0.04% or 0.05%, the content of Cu is 0.00-1.50%, for example, it can be 0.00%, 0.02%, 0.04%, 0.06%, 0.08%, 0.10%, 0.12%, 0.14% or 0.15%, S content is 0.00-0.01%, for example, it can be 0.00%, 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009% or 0.01%, P content is 0.00-0.08%, for example, it can be 0.00%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07% or 0.08%, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. .

[0048] In the present invention, C is the most effective element for improving the strength of steel through interstitial solid solution strengthening. In order to take into account the sufficient precipitation of C and microalloying elements Nb and V, the C content cannot be too low and needs to be higher than 0.2%. At the same time, considering that too high a C content is prone to form brittle twin martensite and deteriorate welding performance. Therefore, the C content is determined to be 0.20-0.30%, and more preferably 0.20-0.28%.

[0049] In the present invention, Si is a solid solution strengthening element. Considering that a high content directly affects the production of dense iron oxide scale on the surface of steel in the hot rolling and annealing stages, such as Si oxides, it is not conducive to pickling removal and the coating effect of aluminum silicon coating, so the Si content is as low as possible. In the smelting stage, in order to remove the O content in the molten steel as much as possible, the Si content is not less than 0.05%. Therefore, the Si content is determined to be 0.05-0.40%, and more preferably 0.10-0.40%.

[0050] In the present invention, Mn has both solid solution strengthening effect and can reduce austenitization temperature, so the Mn content is at least not less than 0.50%. At the same time, considering that too high Mn content is easy to produce serious segregation bands, it is extremely unfavorable to the bending angle and hydrogen embrittlement performance in the TD direction. Therefore, the Mn content is determined to be 0.50-2.00%.

[0051] In the present invention, Cr helps to improve the hardenability of steel, reduce the critical cooling rate of martensite transformation, and ensure that the core layer of hot-formed steel is full martensite. Considering that the iron oxide scale formed by Cr is difficult to remove in the pickling stage, thus affecting the coating quality and the decarburization of the surface of the structure, therefore, the Cr content is determined to be 0.20-1.00%.

[0052] In the present invention, Nb and V can ensure that the required strength is achieved under the condition of suitable C content, and at the same time reduce the welding carbon equivalent, add micro-alloy elements to obtain fine precipitates, and achieve precipitation strengthening effect. In addition, fine precipitates can effectively refine the grain size and improve the bending toughness and hydrogen embrittlement performance of steel. Further, compared with V-containing precipitates, Nb-containing precipitates are more beneficial to hydrogen embrittlement delayed cracking, so it is preferred that the Nb content is as low as 0.01%, and V may not be added.

[0053] In the present invention, B helps to improve the hardenability of the steel, reduce the critical cooling rate at which martensite begins to form, and ensure that the final structure is a full martensite structure. Since adding a small amount of B can significantly improve the hardenability, the B content is determined to be 0.003-0.020%.

[0054] In the present invention, Ti helps to reduce the N in the steel, and prevents N from combining with B to form BN to weaken the hardenability effect of B. Since the N content in the steel is not very high, the Ti content is determined to be 0.01-0.05%.

[0055] In the present invention, Ni helps to reduce the low-temperature brittle transition temperature of high-strength steel. Generally speaking, when the Ni content is less than 0.30%, the brittle transition temperature is below -100°C, so the Ni content is determined to be 0.00-0.30%.

[0056] In the present invention, Mo helps to delay the transformation of austenite to pearlite, improve the hardenability of austenite, and helps to delay the transformation of ε carbide to cementite, inhibiting the temper brittleness of martensite. Considering that a variety of elements with good hardenability, such as Cr, B, etc., are added to the steel, the Mo content is determined to be 0.00-0.05%.

[0057] In the present invention, Al, P and S are impurity elements in the alloy composition system, so the introduction of such elements needs to be reduced as much as possible, and the selection of each alloy element is respectively Al: 0.00-0.50%; P: 0.00-0.08%; S: 0.00-0.01%.

[0058] In some embodiments, measured by mass percentage, C+Al+Si≥1.0%, for example, it may be 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8% or 3.0%, Cr+Mn≤3.0%, for example, it may be 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8% or 3.0%, (Cr+Mn) / (C+Al+Si)≤1.5%, for example, it may be 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4% or 1.5%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0059] In the present invention, considering that Cr and Mn elements will prevent steel from decarburization, and C, Al and Si elements will increase the decarburization tendency of steel, C+Al+Si≥1.0%, Cr+Mn≤3.0%, and (Cr+Mn) / (C+Al+Si)≤1.5% are specifically limited.

[0060] In some embodiments, Nb+V≤0.05% by mass, for example, 0.01%, 0.02%, 0.03%, 0.04% or 0.05%, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0061] In the present invention, in order to ensure that the micro-alloy elements can be fully precipitated, according to the selection of the C content, Nb+V is specifically limited to ≤ 0.05%.

[0062] In some embodiments, the welding carbon equivalent CE=C+Mn / 6+(Cr+Mo+V) / 5+(Ni+Cu) / 15 is less than 0.5% by mass, for example, it can be 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4% or 0.45%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0063] The present invention specifically limits the welding carbon equivalent CE to less than 0.5%, which helps to further improve the welding performance.

[0064] In some embodiments, Si+Cr≤1.2% by mass, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1% or 1.2%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0065] In the present invention, in order to prevent the iron oxide scale from being difficult to remove during the pickling process and to ensure the coating quality, Si+Cr≤1.2% is specifically limited.

[0066] The present invention also provides a method for preparing the hot-formed steel, which satisfies any one or a combination of at least two of the following conditions:

[0067] (A) The coiling temperature after hot rolling is 650-700°C, for example, 650°C, 660°C, 670°C, 680°C, 690°C or 700°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0068] (B) The pickling speed is ≤ 150 m / min, for example, it can be 20 m / min, 40 m / min, 60 m / min, 80 m / min, 100 m / min, 120 m / min, 140 m / min or 150 m / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0069] (C) The temperature of continuous annealing is 780-830°C, for example, 780°C, 790°C, 800°C, 810°C, 820°C or 830°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0070] (D) The atmosphere in the furnace is a mixture of nitrogen and hydrogen.

[0071] (E) The dew point temperature is from -35°C to -17°C, for example, -35°C, -34°C, -33°C, -32°C, -31°C, -30°C, -29°C, -28°C, -27°C, -26°C, -25°C, -24°C, -23°C, -22°C, -21°C, -20°C, -19°C, -18°C or -17°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0072] The present invention specifically limits the coiling temperature after hot rolling to 650-700°C, so as to ensure that the micro-alloy elements have sufficient driving force for precipitation and surface decarburization; considering that the coiling temperature is relatively high and the generated iron oxide scale is relatively thick, the pickling speed is specifically limited to below 150m / min, so as to ensure that the iron oxide scale is completely removed; the specific limitations of the continuous annealing temperature, the furnace atmosphere and the dew point temperature are helpful to further achieve decarburization.

[0073] It can be seen that the present invention realizes sufficient decarburization and refines the grain structure by reasonably adjusting the key preparation conditions of hot-formed steel, further improves the toughness of the material, can replace safety parts with low strength and high toughness, achieves the purpose of weight reduction, and achieves a lightweight effect.

[0074] In some embodiments, the continuous annealing time is 8-12 min, for example, it can be 8 min, 8.5 min, 9 min, 9.5 min, 10 min, 10.5 min, 11 min, 11.5 min or 12 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0075] The present invention also provides an application of the above-mentioned hot-formed steel, wherein the hot-formed steel is used to manufacture automobile body structural parts, including seat crossbeams, A-pillars, B-pillars, door anti-collision beams, front and rear bumpers, door sill beams or center channels.

[0076] The invention uses hot-formed steel to not only maintain or improve the safety and reliability of vehicle body components, but also significantly reduce vehicle weight, improve fuel efficiency, and thus reduce carbon emissions. This innovation will drive the automotive industry toward a more efficient and environmentally friendly direction, achieving a dual breakthrough in technology and materials.

[0077] Examples 1-6

[0078] This group of embodiments respectively provides a 1700MPa grade hot-formed steel with high cold bending performance. The chemical composition of the hot-formed steel is shown in Table 1 below, calculated by mass percentage.

[0079] Table 1

[0080]

[0081]

[0082] The balance is Fe and inevitable impurities.

[0083] According to statistics, the relationship between the chemical components in the hot-formed steel provided in Examples 1-6 is shown in Table 2 below:

[0084] Table 2

[0085]

[0086] In the above table, welding carbon equivalent CE = C + Mn / 6 + (Cr + Mo + V) / 5 + (Ni + Cu) / 15.

[0087] The method for preparing hot-formed steel provided in this group of embodiments comprises the following steps:

[0088] (1) Controlled rolling and controlled cooling

[0089] The continuous casting billet is heated to 1200℃ in a heating furnace and kept warm for 2h, then descaled once to remove the furnace-born iron oxide scale, the rough rolling start temperature is set to 1100±100℃, the finishing rolling start temperature is set to 1040±40℃, the final rolling temperature is set to 920±50℃, and after hot rolling, it is water-cooled to the initial coiling temperature at a cooling rate of 20℃ / s.

[0090] (2) Coiling

[0091] The steel strip is coiled into a steel coil. The coiling temperature of the steel coils in each embodiment is shown in Table 3. Then, the steel strip is slowly air-cooled to room temperature to obtain a hot-rolled steel plate for hot forming after hot rolling and coiling. The hot-rolled steel plate can be used for hot forming. The microstructure of the hot-rolled steel plate after hot rolling and coiling is ferrite, pearlite and a small amount of bainite.

[0092] (3) Pickling and cold rolling

[0093] In order to ensure the quality of the coating and avoid residual iron oxide scale on the surface of the hot-rolled plate, the pickling speed of each embodiment was controlled according to Table 3, and then multiple rolling was performed at room temperature according to the target plate thickness.

[0094] (4) Continuous annealing

[0095] Considering the influence of annealing temperature and dew point on surface decarburization, the continuous annealing temperature, continuous annealing time and dew point temperature of each embodiment are controlled according to Table 3, and the atmosphere in the furnace is N2+H2.

[0096] Specifically, the conditions satisfied by the preparation methods provided in Examples 1-6 are shown in Table 3 below:

[0097] Table 3

[0098]

[0099]

[0100] After testing, the surface layer of the hot-formed steels obtained in Examples 1-6 all had soft-phase ferrite structure, the sub-surface layer all had a mixed structure of soft-phase ferrite and martensite, and the core layer all had a carbon-poor martensite structure (the carbon content was 50%-90% of the target carbon content in the hot-formed steel).

[0101] Specifically, taking the hot-formed steel obtained in Example 1 as an example, the decarburized layer is shown below: Figure 1 , microstructure see below Figure 2 The thickness of the surface layer is about 5μm, the thickness of the sub-surface layer is about 12μm, and the core is carbon-poor martensite.

[0102] After testing, the performance parameters of the hot-formed steel obtained in Examples 1-6 are shown in Table 4 below.

[0103] Table 4

[0104]

[0105] In the above table, the tensile strength test refers to GB / T 228.1-2021 Tensile tests on metallic materials - Part 1: Test methods at room temperature; the bending angle test refers to GB / T 232-2024 Bending test methods for metallic materials; the evaluation of coating quality refers to GB / T 34566-2017 Hot stamped steel sheets and strips for automobiles; the evaluation of welding performance refers to GB / T 39167-2020 Tensile shear test methods for resistance spot welding and projection welding joints.

[0106] Taking the conventional 22MnB5 hot-formed steel as a comparative example, the tensile and bending curves of the hot-formed steel obtained in Example 1 are shown below: Figure 3 .

[0107] Depend on Figure 3 It can be seen that compared with the traditional 22MnB5 hot-forming steel, the tensile and bending properties of the hot-forming steel obtained in Example 1 show obvious advantages. The tensile and bending properties of the hot-forming steels obtained in Examples 2-6 are similar to those in Example 1, so they are not described here in detail.

[0108] It can be seen that the present invention changes the distribution characteristics of the traditional full martensitic structure, introduces 5-40μm ferrite and a mixed structure of ferrite and martensite into the surface layer of the hot-formed steel, and reasonably adjusts the key preparation conditions of the hot-formed steel, thereby achieving sufficient decarburization and refined grain structure, and finally obtaining a hot-formed steel with high cold bending performance of 1700MPa. While ensuring that the strength is 200MPa higher than that of commercial 1500MPa hot-formed steel, the bending toughness is equivalent, which successfully solves the contradiction between material strength and toughness, achieves the dual guarantee of high strength and high toughness, meets the lightweight requirements, and improves the competitiveness of existing products.

[0109] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A 1700MPa grade hot-formed steel with high cold bending performance, characterized in that: The hot-formed steel has a surface layer with a soft-phase ferrite structure, a sub-surface layer with a mixed structure of soft-phase ferrite and martensite, and a core layer with a carbon-poor martensite structure; Wherein, the thickness of the surface layer is 0-20 μm, and the thickness of the sub-surface layer is 5-20 μm; The tensile strength of the hot-formed steel is 1650-1750 MPa.

2. The hot-formed steel according to claim 1, characterized in that: The carbon content of the carbon-poor martensite structure is 50%-90% of the target carbon content in the hot-forming steel; The core layer also has a ferrite structure, and the proportion of the ferrite structure in the core layer is ≤5%.

3. The hot-formed steel according to claim 1, characterized in that: The chemical composition of the hot-formed steel includes, by mass percentage:

4. The hot-formed steel according to claim 3, characterized in that: Calculated by mass percentage, C+Al+Si≥1.0%, Cr+Mn≤3.0%, (Cr+Mn) / (C+Al+Si)≤1.5%.

5. The hot-formed steel according to claim 3, characterized in that: In terms of mass percentage, Nb+V≤0.05%.

6. The hot-formed steel according to claim 3, characterized in that: Calculated in terms of mass percentage, welding carbon equivalent CE=C+Mn / 6+(Cr+Mo+V) / 5+(Ni+Cu) / 15<0.5%.

7. The hot-formed steel according to claim 3, characterized in that: In terms of mass percentage, Si+Cr≤1.2%.

8. A method for preparing hot-formed steel according to any one of claims 1 to 7, characterized in that: The preparation method satisfies any one or a combination of at least two of the following conditions: (A) The coiling temperature after hot rolling is 650-700℃; (B) Pickling speed ≤ 150m / min; (C) The temperature of continuous annealing is 780-830°C; (D) The atmosphere in the furnace is a mixture of nitrogen and hydrogen; (E) The dew point temperature is -35°C to -17°C.

9. The preparation method according to claim 8, characterized in that: The continuous annealing time is 8-12 minutes.

10. An application of the hot-formed steel according to any one of claims 1 to 7, characterized in that: The hot-formed steel is used to manufacture body structural parts of automobiles, including seat crossbeams, A-pillars, B-pillars, door anti-collision beams, front and rear bumpers, door sill beams or center channels.

Citation Information

Patent Citations

  • Steel for hot stamping forming, hot stamping forming process and hot stamping forming component

    CN106399837A

  • High-toughness hot-formed steel and production method thereof

    CN106947919A

  • Aluminum-silicon coating hot stamping forming component and preparation method and application thereof

    CN116174558A

  • Hot-pressed steel sheet member, production method for same, and hot-press steel sheet

    CN105849294A

  • Hot-forming component with tensile strength being above 1800MPa grade and excellent cold bending performance, and preparation method thereof

    CN110423953A

Cited By

  • 1700 mpa grade hot-formed steel having excellent cold bending performance, preparation method therefor and use thereof

    WO2026113985A1